Pengaruh Kalium dan Varietas Jagung terhadap Eksudat Asam Organik dari Akar, Serapan N, P, dan K Tanaman dan Produksi Brangkasan Jagung (Zea mays L.) - Dedi Nursyamsi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
Pot experiment was aimed to study effect of potassium (K) and variety on organic acid exudates from roots, plant N, P, and K uptakes, and plant dry weight. The experiment was conducted in the green house of Indonesian Soil Research Institute, Bogor using sand culture method. Factorial in Completely Randomized Block Design with three replications was used in this experiment. The first factor was K application, i.e. without K and application of 100 ppm K, and the second one was 10 varieties of maize, i.e. Antasena, Sukmaraga, CIMMIT 3330, Wisanggeni, Bisma, Lamuru, Pioneer-4, Pioneer-7, Pioneer-11, and Pioneer-21. The result showed that application of K significantly increased plant N and K uptakes. Among tested varieties, the N, P, and K uptake, as well as roots and dry weights of CIMMIT 3330 were the lowest, while those variables of Pioneer-7 were the highest. Among organic acid exudates, oxalic acid was the most dominant exudates exerted from roots, it was about 3.15 mg/g roots dry weight (DW) of Wisanggeni compared to 5.93 mg/g roots DW of CIMMIT 3330. Plant age significantly affected the exudates which was in the order of 4 weeks after planting (WAP) > 2 WAP > 6 WAP. Among tested varieties (Antasena, CIMMIT 3330, Wisanggeni, Lamuru, and Pioneer-21), CIMMIT 3330 was the most potential variety to increase availability of soil K in smectitic soils, thus increasing the efficiency of K fertilizer in the soils. Key words: Potassium, variety, organic acid exudates, plant uptake, maize.